Preparation method of lithium ion battery negative electrode material based on metal organic framework structure silicon material and application thereof
Patent Information
- Application Number
- CN202510391666.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-03-31
AI Technical Summary
本发明所制备的锂离子电池负极材料,解决硅材料在锂离子电池应用中的体积膨胀问题,同时提高材料的比容量、循环稳定性和倍率性能
[0024]本发明所制备的基于金属有机框架结构硅材料的锂离子电池负极材料通过多级孔隙缓冲硅体积膨胀,提高电池的循环稳定性,500次容量保持率>95%。通过构建梯度碳层提升导电性,比容量达2060.1mAh/g,本发明所制备的基于金属有机框架结构硅材料的锂离子电池负极材料适用于高能量密度锂离子电池负极片,能够显著延长电池寿命。
Smart Images

Figure CN120423558B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a method for preparing lithium-ion battery anode materials based on silicon materials with a metal-organic framework structure and their application. Background Technology
[0002] Lithium-ion batteries, with their high energy density, long cycle life, and environmentally friendly characteristics, have been widely used in consumer electronics, electric vehicles, and energy storage systems. However, the theoretical specific capacity of traditional graphite anode materials is relatively low (approximately 372 mAh / g), making it difficult to meet the ever-increasing demand for high energy density. In contrast, silicon materials are considered an ideal choice for next-generation anode materials due to their theoretical specific capacity of up to 4200 mAh / g. However, during charge and discharge, silicon materials undergo severe volume expansion (approximately 300%), leading to electrode pulverization, capacity decay, and shortened cycle life.
[0003] While silicon-carbon composite materials and nanostructured silicon have been used to alleviate the volume expansion problem in existing technologies, these methods still have many shortcomings. For example, silicon-carbon composite materials offer limited capacity improvement and poor rate performance; nanostructured silicon is expensive to prepare, making large-scale application difficult; furthermore, the insufficient optimization of lithium-ion transport by traditional materials also limits the improvement of battery performance to some extent.
[0004] Metal-organic frameworks (MOFs) have shown great potential in energy storage due to their high specific surface area, tunable pore structure, and good chemical stability. However, when MOFs are used directly as anode materials, they suffer from low capacity and poor conductivity. Therefore, developing lithium-ion battery anode materials with superior performance is crucial for advancing battery technology. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing lithium-ion battery anode materials based on metal-organic framework silicon materials and their applications. The lithium-ion battery anode material prepared by this invention solves the volume expansion problem of silicon materials in lithium-ion battery applications, while simultaneously improving the material's specific capacity, cycle stability, and rate performance.
[0006] The technical solution of the present invention is as follows:
[0007] A method for preparing a lithium-ion battery anode material based on a metal-organic framework silicon material, the method comprising the following steps:
[0008] (1) Preparation of MOF materials: Zinc ions and organic ligands are dissolved in a solvent to obtain a precursor solution, and then the MOF precursor is obtained by solvothermal reaction, and the MOF material is obtained by drying.
[0009] (2) Deposition of silicon material: Silicon material is uniformly distributed in the pores of MOF material using plasma-assisted pulsed gradient chemical vapor deposition to obtain MOF-Si material;
[0010] The plasma-assisted pulsed gradient chemical vapor deposition method is implemented in three steps, including a silicon material pre-decomposition stage, a diffusion stage, and a crystallization process.
[0011] (3) Preparation of carbon coating layer: A carbon coating layer is formed on the surface of MOF-Si material by chemical vapor deposition or high temperature pyrolysis, and after high temperature annealing, MOF-Si-C composite material is obtained, which is the negative electrode material of lithium-ion battery.
[0012] Further, in step (1), the organic ligand is selected from either terephthalic acid or 2-methylimidazole; the solvent is selected from either DMF or methanol; the concentration of zinc ions in the solvent is 0.1-0.5 mol / L; and the molar ratio of zinc ions to organic ligand is 1:1-3.
[0013] Further, in step (1), the reaction temperature is 80-150℃; the pressure is 0.5-3 MPa; the time is 12-48 h; the drying method is supercritical CO2 drying technology, the temperature is 40-60℃, and the time is 6-12 h.
[0014] Further, in step (2), the silicon material includes either silicon nanoparticles or silane precursors.
[0015] Further, in step (2), the flow rate of the silicon material in the pre-decomposition stage is 8-10 sccm, the temperature is 300-400℃, the deposition rate is 0.8-1.0 nm / min, and the deposition time is 30-50 min;
[0016] The diffusion stage employs a three-temperature gradient control, with a heating rate of 4-6℃ / min. The temperature is first increased from 300℃ to 440-460℃, held for 30-50 minutes, and then further increased to 540-560℃. H2 carrier gas is used to propel the silicon material through the mesoporous channels of the MOF material, with a processing time of 60-80 minutes. The flow rate of H2 is 15-25 sccm.
[0017] The crystallization stage employs pulsed Si₂H₆-assisted gas combined with laser irradiation to induce directional rearrangement of silicon atoms; the temperature of the crystallization stage is 540-560℃, and the time is 30-50 min; the pulse period is 10 s on / 5 s off; the laser irradiation wavelength is 520-540 nm, and the power density is 25-35 mW / cm². 2 .
[0018] Further, in step (3), the carbon coating layer has a three-layer structure, consisting of a PDA transition layer, a graphene layer, and a carbon nanotube network layer from the inside out; the thickness ratio of the PDA transition layer, the carbon nanotube network layer, and the graphene layer is 2:3:8; and the thickness of the carbon coating layer is 13-15 nm.
[0019] In a further step (3), the MOF-Si-C composite material has a multi-level pore structure, including micropores, mesopores and macropores; the porosity of the MOF-Si-C composite material is >85%.
[0020] Furthermore, the proportion of micropores is 60-65%; the proportion of mesopores is 30-35%; and the proportion of macropores is 5-10%.
[0021] An application of the lithium-ion battery anode material prepared by the aforementioned preparation method, wherein the lithium-ion battery anode material is used to prepare lithium-ion battery anode sheets.
[0022] Furthermore, the application method is as follows: the lithium-ion battery negative electrode material, conductive agent and binder are mixed and made into a slurry, coated on copper foil, and after drying and pressing, a lithium-ion battery negative electrode sheet is obtained.
[0023] The beneficial technical effects of this invention are as follows:
[0024] The lithium-ion battery anode material based on a metal-organic framework silicon structure prepared in this invention improves the cycle stability of the battery by buffering silicon volume expansion through multi-level pores, achieving a capacity retention rate of >95% after 500 cycles. By constructing a gradient carbon layer to enhance conductivity, a specific capacity of 2060.1 mAh / g is achieved. This lithium-ion battery anode material based on a metal-organic framework silicon structure prepared in this invention is suitable for high-energy-density lithium-ion battery anode sheets and can significantly extend battery life.
[0025] Compared to traditional silicon-carbon anodes, which have a simple pore structure (mainly mesopores) and cannot simultaneously achieve high specific capacity and expansion suppression, this invention, through the synergistic effect of multi-level pores, achieves for the first time a silicon-based anode with a capacity retention of >95% after 500 cycles.
[0026] This invention achieves a synergistic improvement in specific capacity (2060.1 mAh / g), cycle stability (>95% after 500 cycles), and conductivity (impedance <20Ω) through multi-level pores, CVD silicon deposition, and gradient carbon coating technology, thereby significantly improving the electrochemical performance of the battery. Attached Figure Description
[0027] Figure 1 This is a SEM image of the lithium-ion battery anode material prepared in Example 1 of the present invention.
[0028] Figure 2The AC impedance test diagrams are for coin cells prepared using the lithium-ion battery negative electrode sheets of Application Example 1 and Comparative Examples 3-4 of this invention.
[0029] Figure 3 The charge-discharge curves are shown for the coin cells prepared using the lithium-ion battery negative electrode sheets of Application Example 1 and Comparative Examples 3-4 of this invention. Detailed Implementation
[0030] The present invention will now be described in detail with reference to the accompanying drawings and embodiments.
[0031] In this invention, the porosity of the material was determined by a combination of nitrogen adsorption-desorption isotherm (BET method) and mercury porosimetry; the micropore distribution was analyzed using the Horvath-Kawazoe (HK) model; the mesopore distribution was calculated using the Barrett-Joyner-Halenda (BJH) model; the macropore structure was characterized by mercury porosimetry under a high pressure of 414 MPa; and the overall pore volume distribution was verified by small-angle X-ray scattering (SAXS).
[0032] Example 1
[0033] A method for preparing a lithium-ion battery anode material based on a metal-organic framework silicon material is as follows:
[0034] (1) Preparation of MOF material: 0.08 mol of zinc nitrate and 0.08 mol of terephthalic acid were dissolved in 200 mL of DMF and stirred until dissolved to obtain a precursor solution. The precursor was then reacted at 120 °C and 1.5 MPa for 30 h by a solvothermal method to obtain the MOF precursor. The MOF material was obtained by supercritical CO2 drying at 50 °C for 9 h.
[0035] (2) Silicon deposition: Silicon is loaded using plasma-assisted pulsed gradient chemical vapor deposition (PCVD) process.
[0036] ① In the pre-decomposition stage, a SiH4 / Ar mixed gas (SiH4 content 5%) is introduced at a flow rate of 10 sccm and excited and decomposed at 300℃ by radio frequency plasma (power 50W, frequency 13.56MHz) to form 2-3nm silicon quantum dot clusters (deposition rate 0.8nm / min). The processing time is 30min.
[0037] ②Diffusion stage: Three-temperature gradient control is adopted. The temperature is increased from 300℃ to 450℃ at a rate of 5℃ / min, held for 40min, and then increased to 550℃. Silicon atoms are driven to penetrate along the mesoporous channels of MOF material (penetration depth > 200μm) by H2 carrier gas (flow rate 20sccm). The treatment time is 60min.
[0038] ③ During the crystallization stage, a pulsed Si2H6 auxiliary gas (pulse period 10s on / 5s off) is introduced into an argon atmosphere at 550℃, while simultaneously operating at a wavelength of 532nm and a flow rate of 30mW / cm². 2 Laser irradiation at a power density for 30 minutes induces silicon atoms to rearrange in an oriented manner, ultimately obtaining a β-Si phase with a crystallinity >95% (XRD half-width 0.12°), thus yielding MOF-Si material.
[0039] (3) Preparation of carbon coating layer: A carbon coating layer was constructed on the surface of MOF-Si material by plasma-enhanced pulsed chemical vapor deposition: First, 0.25g of polydopamine was mixed with 5g of MOF-Si material and self-assembled to form a monolayer polydopamine transition layer (2nm) on the surface of MOF-Si material as an interface reinforcement layer. Subsequently, the material was activated by argon / hydrogen plasma at 400℃ and 50Pa, and acetylene (5ms pulse) and methane (20ms pulse) were introduced by alternating pulse mode, thereby directionally growing wrinkled graphene (8nm) with nitrogen-doped sites on the amorphous carbon matrix; then, the material was activated by argon / hydrogen plasma at 800℃ and 50Pa, and 8g of FeCo@Mo bimetallic catalyst was added, and acetylene (5ms pulse) and methane (20ms pulse) were introduced by alternating pulse mode, forming a composite network of monolayer helical carbon nanotubes (3nm); the thickness of the carbon layer was precisely controlled at the nanometer level by in-situ laser annealing technology. Finally, the MOF-Si-C composite material was obtained by high-temperature pyrolysis at 800℃ for 2 hours, which is the lithium-ion battery anode material (scanning electron microscope image as shown). Figure 1 (As shown).
[0040] Testing revealed that the graphene has 3-5 layers with an interlayer spacing of 0.38 nm; the single-layer helical carbon nanotube network has a unique double-walled to triple-walled alternating structure (inner wall spacing 0.34 nm, outer wall spacing 0.39 nm), a tube diameter of 6-8 nm, and an axial periodic bamboo-like morphology (internode spacing 10-15 nm).
[0041] The pore structure of the MOF-Si-C composite material exhibits a multi-level distribution: micropores (<2nm) account for 65%, mesopores (2-50nm) account for 30%, and macropores (>50nm) account for approximately 5%. The silicon crystallization process transforms 5-15% of the micropores into mesopores (pore size 2-5nm), but the graphene / carbon nanotube composite structure coating inhibits the collapse of the pore structure. Atomic force microscopy (AFM) phase imaging verification shows that the composite carbon layer exhibits a gradient thickness distribution of 13±2nm (3nm of surface carbon nanotube network, 8nm of middle dense graphene, and 2nm of bottom PDA transition layer), ultimately maintaining a porosity of 90%.
[0042] Example 2
[0043] (1) Preparation of MOF material: 0.02 mol zinc nitrate and 0.02 mol terephthalic acid were dissolved in 200 mL DMF and stirred until dissolved to obtain a precursor solution. The precursor solution was then reacted at 80 °C and 0.5 MPa for 12 h by a solvothermal method and dried at 40 °C with supercritical CO2 for 6 h to obtain MOF material.
[0044] (2) Silicon deposition: Silicon is loaded using plasma-assisted pulsed gradient chemical vapor deposition (PCVD) process.
[0045] ① In the pre-decomposition stage, SiH4 / Ar (SiH4 content 5%) is introduced at a flow rate of 8 sccm and treated with radio frequency plasma (50W, 13.56MHz) at 300℃ for 30 min to form 2-3nm silicon quantum dot clusters (deposition rate 0.8nm / min).
[0046] ②Diffusion stage: Three-temperature gradient control is adopted. The temperature is increased from 300℃ to 450℃ at a rate of 5℃ / min, held for 40min, and then increased to 550℃. Silicon atoms are permeated by H2 carrier gas (flow rate 20sccm) for 60min.
[0047] ③ During the crystallization stage, a pulsed Si2H6 auxiliary gas (pulse period 10s on / 5s off) was introduced into an argon atmosphere at 550℃, at a wavelength of 532nm and a flow rate of 30mW / cm². 2 Laser irradiation at a power density for 30 minutes induces silicon atoms to rearrange in an oriented manner, ultimately obtaining a β-Si phase with a crystallinity >95% (XRD half-width 0.12°), thus yielding MOF-Si material.
[0048] (3) Preparation of carbon coating layer: A carbon coating layer was constructed on the surface of MOF-Si material by plasma-enhanced pulsed chemical vapor deposition: First, 0.2g of polydopamine was mixed with 5g of MOF-Si material and self-assembled to form a monolayer polydopamine transition layer (2nm) on the surface of MOF-Si material as an interface reinforcement layer. Subsequently, the material was activated by argon / hydrogen plasma at 400℃ and 50Pa, and acetylene (5ms pulse) and methane (20ms pulse) were introduced by alternating pulse mode, thereby directionally growing wrinkled graphene (8nm) with nitrogen-doped sites on the amorphous carbon matrix; then, the material was activated by argon / hydrogen plasma at 800℃ and 50Pa, and 8g of FeCo@Mo bimetallic catalyst was added, and acetylene (5ms pulse) and methane (20ms pulse) were introduced by alternating pulse mode, forming a composite network of monolayer helical carbon nanotubes (3nm); the thickness of the carbon layer was precisely controlled at the nanometer level by in-situ laser annealing technology. Finally, the MOF-Si-C composite material, i.e., the lithium-ion battery anode material, was obtained by treating it at 800℃ for 2 hours using a high-temperature pyrolysis method.
[0049] The pore structure of the MOF-Si-C composite material exhibits a multi-level distribution: micropores (<2nm) account for 60%, mesopores (2-50nm) account for 35%, and macropores (>50nm) account for approximately 5%. Atomic force microscopy (AFM) phase imaging verified that the composite carbon layer exhibits a gradient thickness distribution of 13±2nm (the surface 3nm is a carbon nanotube network, the middle 8nm is dense graphene, and the bottom 2nm is a PDA transition layer), with a porosity of 86%.
[0050] Example 3
[0051] (1) Preparation of MOF material: 0.1 mol zinc nitrate and 0.3 mol 2-methylimidazole were dissolved in 200 mL methanol and stirred until dissolved to obtain a precursor solution. The precursor solution was then reacted at 150 °C and 3 MPa for 48 h by a solvothermal method and dried at 60 °C with supercritical CO2 for 12 h to obtain MOF material.
[0052] (2) Silicon deposition: Silicon is loaded using plasma-assisted pulsed gradient chemical vapor deposition (PCVD) process.
[0053] ① In the pre-decomposition stage, SiH4 / Ar (SiH4 content 5%) is introduced at a flow rate of 10 sccm and treated with radio frequency plasma (50W, 13.56MHz) at 400℃ for 50 min to form 2-3nm silicon quantum dot clusters (deposition rate 1.0nm / min).
[0054] ②Diffusion stage: Three-temperature gradient control is adopted. The temperature is increased from 300℃ to 450℃ at a rate of 5℃ / min, held for 40min, and then increased to 550℃. Silicon atoms are permeated by H2 carrier gas (flow rate 20sccm) for 80min.
[0055] ③ During the crystallization stage, a pulsed Si2H6 auxiliary gas (pulse period 10s on / 5s off) was introduced into an argon atmosphere at 550℃, at a wavelength of 532nm and a flow rate of 30mW / cm². 2 Laser irradiation at a power density for 50 min induces silicon atom directional rearrangement, ultimately obtaining a β-Si phase with a crystallinity >95% (XRD half-width 0.12°), thus yielding MOF-Si material.
[0056] (3) Preparation of carbon coating layer: A carbon coating layer was constructed on the surface of MOF-Si material by plasma-enhanced pulsed chemical vapor deposition: First, 0.3g of polydopamine was mixed with 5g of MOF-Si material and self-assembled to form a monolayer polydopamine transition layer (2nm) on the surface of MOF-Si material as an interface reinforcement layer. Subsequently, the material was activated by argon / hydrogen plasma at 400℃ and 50Pa, and acetylene (5ms pulse) and methane (20ms pulse) were introduced by alternating pulse mode, thereby directionally growing wrinkled graphene (8nm) with nitrogen-doped sites on the amorphous carbon matrix. Then, the material was activated by argon / hydrogen plasma at 800℃ and 50Pa, and 8g of FeCo@Mo bimetallic catalyst was added. Acetylene (5ms pulse) and methane (20ms pulse) were introduced by alternating pulse mode, forming a composite network of monolayer helical carbon nanotubes (3nm). The thickness of the carbon layer was precisely controlled at the nanometer level by in-situ laser annealing technology. Finally, the MOF-Si-C composite material, i.e., the lithium-ion battery anode material, was obtained by treating it at 800℃ for 2 hours using a high-temperature pyrolysis method.
[0057] The pore structure of the MOF-Si-C composite material exhibits a multi-level distribution: micropores (<2nm) account for 65%, mesopores (2-50nm) account for 30%, and macropores (>50nm) account for 5%. Atomic force microscopy (AFM) phase imaging verified that the composite carbon layer exhibits a gradient thickness distribution of 13±2nm (the surface 3nm is a carbon nanotube network, the middle 8nm is dense graphene, and the bottom 2nm is a PDA transition layer), with a porosity of 88%.
[0058] Application Example 1
[0059] The preparation of lithium-ion battery anode sheets is as follows:
[0060] The MOF-Si-C composite material prepared in Example 1, SuperP conductive agent, and polyvinylidene fluoride (PVDF) binder were mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) solvent was added to form a slurry. The slurry was coated on copper foil, dried, and then pressed into a sheet to obtain a lithium-ion battery negative electrode sheet.
[0061] Comparative Example 1
[0062] A method for preparing MOF-C composite material based on lithium-ion battery anode material is as follows:
[0063] (1) Preparation of MOF materials: The process is basically the same as step (1) in Example 1, except that conventional vacuum drying at 60°C for 24 hours is used instead of the supercritical CO2 drying method in Example 1.
[0064] (2) Preparation of carbon coating layer: Same as step (3) in Example 1.
[0065] Testing revealed that capillary forces caused pore collapse during the drying process, and the carbon coating layer was applied directly without silane precursor treatment, resulting in a final porosity of only 68% and a BET specific surface area reduced to 950 m². 2 / g. Pore structure analysis showed that the proportion of micropores dropped sharply to 38% (<2nm), mesopores increased abnormally to 52% (2-50nm), and macropores accounted for 10% (>50nm).
[0066] Comparative Example 2
[0067] A method for preparing a lithium-ion battery anode material based on a metal-organic framework silicon material is as follows:
[0068] (1) Preparation of MOF materials: Same as step (1) in Example 1.
[0069] (2) Silicon material deposition: Silicon was loaded using conventional thermal CVD: pure SiH4 (20 sccm) was continuously introduced at a constant temperature of 550℃, the deposition rate was 1.2 nm / min, and the deposition time was 60 min.
[0070] (3) Preparation of carbon coating layer: A homogeneous carbon layer (25 nm thick) without carbon nanotube structure was grown by CVD using a single methane source. After treatment at 800℃ for 2 h, the lithium-ion battery anode material was obtained.
[0071] Testing revealed that high temperatures caused rapid agglomeration of silicon particles (50-80 nm in diameter), clogging the MOF pores. Ultimately, the micropore percentage decreased to 47%, with micropores <1 nm completely disappearing; the BET specific surface area was 1200 m². 2 / g. Mercury intrusion porosimetry showed that the 30-50 nm mesopores were blocked by silicon particles (cumulative pore volume reduction of 38%), and SAXS confirmed that the pore tortuosity index increased to 4.7.
[0072] Comparative Example 3
[0073] A method for preparing a lithium-ion battery anode material is as follows:
[0074] 0.2 mol of silicon nanoparticles were immersed in 500 mL of methanol solution containing 0.4 mol / L zinc nitrate and 0.8 mol / L 2-methylimidazole, and allowed to stand at room temperature for 24 h. The product was washed with methanol and dried to obtain silicon material based on the ZIF-8 structure.
[0075] Comparative Example 4
[0076] A method for preparing a lithium-ion battery anode material is as follows:
[0077] 0.1 mol of mesoporous silica (MCM-41 type, Sigma-Aldrich product number 643645) was immersed in 500 mL of toluene solution containing 0.1 mol / L 3-aminopropyltriethoxysilane and refluxed for 12 h. The product was washed with toluene and dried to obtain amino-modified mesoporous silica. The amino-modified mesoporous silica was then immersed in 500 mL of N,N-dimethylformamide solution containing 0.3 mol / L copper nitrate and 1.0 mol / L trimesic acid and reacted at 80 °C for 24 h. The product was washed with N,N-dimethylformamide and dried to obtain a silicon material based on the HKUST-1 structure.
[0078] Application Comparative Example 1
[0079] The preparation method for lithium-ion battery anode sheets is basically the same as that in Application Example 1, except that the MOF-C composite material prepared in Comparative Example 1 is used instead of the MOF-Si-C composite material. All other contents remain unchanged.
[0080] Application Comparative Example 2
[0081] The preparation method for lithium-ion battery anode sheets is basically the same as that in Application Example 1, except that the lithium-ion battery anode material prepared in Comparative Example 2 is used to replace the MOF-Si-C composite material, and the rest remains unchanged.
[0082] Application Comparative Example 3
[0083] The preparation method for lithium-ion battery anode sheets is basically the same as that in Application Example 1, except that the ZIF-8 structured silicon material prepared in Comparative Example 3 is used to replace the MOF-Si-C composite material. All other aspects remain unchanged.
[0084] Application Comparative Example 4
[0085] The preparation of lithium-ion battery anode sheets is as follows:
[0086] The silicon material based on the HKUST-1 structure prepared in Comparative Example 4, acetylene black conductive agent and sodium carboxymethyl cellulose (CMC) binder were mixed in a mass ratio of 7:2:1, and N-methylpyrrolidone (NMP) solvent was added to make a slurry. The slurry was coated on copper foil, dried and pressed into a sheet to obtain a lithium-ion battery negative electrode sheet.
[0087] Test case
[0088] (1) Characterization of the structure of lithium-ion battery anode materials
[0089] The specific surface area, porosity, and pore size distribution characteristics of the lithium-ion battery anode materials prepared in Example 1 and Comparative Examples 1-2 of this invention were tested, and the results are shown in Table 1.
[0090] Table 1 Structural Characterization
[0091]
[0092] As can be seen from Table 1, the lithium-ion battery anode material prepared by drying the MOF precursor with supercritical CO2 drying, depositing silicon material by plasma-assisted pulsed gradient chemical vapor deposition, and a three-layer carbon coating can significantly improve the BET specific surface area of the material, avoid pore collapse, maintain the proportion of micropores, and thus improve the material performance.
[0093] (2) Impedance test of lithium-ion battery negative electrode
[0094] The impedance performance of the lithium-ion battery negative electrode corresponding to the application examples and comparative examples of this invention was tested using coin cells.
[0095] Button cell fabrication method: In a glove box, lithium-ion battery negative electrode, Celgard 2400 polypropylene separator, and lithium metal sheet are stacked to ensure isolation between the two electrodes. 300 μL of 1M LiPF6 EC / DMC / DEC (1:2:1 v / v) electrolyte is injected, and the cells are sealed under vacuum to form a CR2032 type button cell.
[0096] The impedance of the coin cells prepared using the lithium-ion battery anode sheets of Examples 1 and 3-4 of this invention was measured using an electrochemical workstation. The results are as follows: Figure 2 As shown. From Figure 2 The results show that the coin cell corresponding to the lithium-ion battery negative electrode sheet prepared in Example 1 of this invention has the lowest high-frequency and low-frequency impedance. This is because the gradient carbon coating in the MOF-Si-C composite material reduces the interfacial impedance and provides porous support and lithium-ion transport channels. In addition, the silicon material distributed in the MOF channels can effectively provide expansion margin for the structural changes caused by volume expansion. Furthermore, the graphene / carbon nanotube composite structure coated on the surface of the MOF structure also improves the conductivity and structural stability of the material, thereby reducing impedance. The synergistic effect produced by this structure achieves excellent electrochemical performance.
[0097] (3) Peel force test:
[0098] The lithium-ion battery anode sheets prepared in the application examples and application comparisons were peeled 180° to measure the adhesion performance between the anode coating material and the current collector (copper foil) by peel strength.
[0099] An intelligent electronic tensile testing machine was used to evaluate the adhesion of the coating to the electrode surface by measuring the force required to peel the coating off the copper foil surface using adhesive tape. During the test, the test piece was clamped in the lower fixture, which remained stationary. The free end of the copper foil was fixed in the upper fixture, and the adhesive tape used to apply the coating was fixed in the lower fixture. The lower fixture moved upwards at a set speed, causing the adhesive tape to peel the coating off the foil surface. A force sensor in the upper fixture recorded the force generated during the peeling process in real time, and the average force value was recorded as the peeling force of the electrode coating. The results are shown in Table 2.
[0100] Table 2 Peeling Force
[0101] Example 1 15.3 Comparative Example 1 5.2 Comparative Example 2 8.1 Comparative Example 3 3.7 Comparative Example 4 4.5
[0102] As shown in Table 2, the lithium-ion battery anode sheet prepared using the method of this invention exhibits high glass strength and superior adhesion performance. This invention enhances the performance of the lithium-ion battery anode sheet through the synergistic effect of gradient carbon coating layers. Specifically, the PDA transition layer enhances the bonding strength between the carbon layer and the MOF-Si interface (peel force >15 N / m). This is due to the coordination bonding of the catechol groups of polydopamine with the MOF surface, forming strong chemisorption (FTIR shows CO-Zn bond characteristic peaks). Simultaneously, the carbon nanotube network layer constructs a three-dimensional conductive pathway, reducing charge transfer impedance (<20 Ω). This is because the FeCo@Mo bimetallic catalyst induces the carbon nanotubes to form a helical structure (TEM shows a helical angle of 15-20°), increasing the number of conductive contact points (EIS shows a 70% reduction in interfacial impedance). Furthermore, the graphene layer can suppress electrode pulverization caused by silicon volume expansion and stabilize the SEI film. This is because the wrinkled graphene (0.38 nm interlayer spacing) mechanically restricts the displacement of silicon particles (AFM shows surface deformation <5 nm), and its hydrophobicity reduces side reactions (XPS shows LiF content in SEI increased to 35%). Compared to traditional single carbon coatings, which lack gradient design and cannot balance conductivity and mechanical strength (carbon layer cracking rate >30% after cycling), the gradient carbon layer of this invention results in a cracking rate of <5%.
[0103] (4) Electrochemical performance characterization of lithium-ion battery anode
[0104] The electrochemical performance of the lithium-ion battery anode sheets corresponding to the application examples and comparative examples of this invention was tested using coin cells. The results are shown in Table 3 and the attached figures. The specific test methods are as follows:
[0105] Button cell fabrication method: In a glove box, lithium-ion battery negative electrode, Celgard 2400 polypropylene separator, and lithium metal sheet are stacked to ensure isolation between the two electrodes. 300 μL of 1M LiPF6 EC / DMC / DEC (1:2:1 v / v) electrolyte is injected, and the cells are sealed under vacuum to form a CR2032 type button cell.
[0106] Electrochemical tests were conducted at room temperature (25±1)℃. A LAND CT2001A battery charge / discharge instrument was used to test specific capacity, rate performance, and cycle performance via constant current charge / discharge. The results are shown in Table 1 and attached figures. The cycle performance measurement refers to the reversible capacity after 500 cycles. The current used for testing the charge / discharge capacity was 0.5C. Test parameters were set as follows: charge / discharge voltage range from 0.01V to 3.0V.
[0107] Rate performance testing primarily involves measuring the charge-discharge capacity of lithium-ion batteries at different currents at room temperature. Currents were set at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C, and then back to 0.1C. The main purpose was to test the battery's charge-discharge performance under high current by performing high-current tests followed by low-current tests at 0.1C, thereby exploring the stability of the materials.
[0108] The electrochemical impedance spectroscopy (EIS) test was performed using a CHI760E electrochemical workstation manufactured by Shanghai Chenhua Instrument Co., Ltd. The test frequency range was 0.01Hz-1000kHz, and the amplitude was 5mV.
[0109] Table 3 Electrochemical Performance
[0110]
[0111] As shown in Table 3, the lithium-ion battery anode sheet prepared using the method of this invention exhibits higher charge-discharge specific capacity, higher initial efficiency, and more stable long cycle life performance compared to the comparative sample. The MOF-Si-C composite material of this invention possesses a multi-level porous structure. Micropores (<2nm) account for 60-65%, providing an ultra-high specific surface area (>2200m²). 2 The micropores expose more lithium-ion adsorption sites, thus increasing the specific capacity of the material. This is because the micropores physically confine silicon nanoparticles (2-5 nm in diameter), preventing their aggregation, and their narrow channels shorten the lithium-ion diffusion path (increasing the diffusion coefficient to 3 × 10⁻¹⁰ cm⁻¹). 2The mesopores (2-50nm) comprise 30-35% of the structure, buffering the volume expansion of silicon during lithium insertion / extraction (expansion rate reduced from 300% to 120%) and suppressing electrode pulverization. This is because the mesopores act as "elastic spaces" to accommodate silicon expansion, and their tortuous channels disperse stress concentration (finite element simulations show a 65% reduction in peak stress), preventing channel collapse. The macropores (>50nm) comprise 5-10%, promoting electrolyte penetration and improving ion transport efficiency (ionic conductivity >8.5×10⁻³ S / cm). This is because the macropores form a three-dimensional interconnected network, shortening the electrolyte wetting path (penetration time reduced from 30 min to 5 min) and accelerating lithium-ion migration through capillary action.
[0112] Figure 3 The specific capacity of the lithium-ion battery negative electrode used in coin cells is as follows: Figure 3 As shown. From Figure 3 The results show that the lithium-ion battery anode sheet prepared in Example 1 of this invention exhibits the highest specific capacity (2060.1 mAh / g) and a first-cycle efficiency of 91.6%. This is because the high theoretical specific capacity of silicon material combined with the high specific surface area of MOF structure significantly improves the specific capacity of the anode material. At the same time, the porosity of MOF structure can effectively alleviate the volume expansion of silicon material during charging and discharging (reduced to 120%), and the carbon coating layer also enhances the conductivity of the material.
[0113] This invention employs plasma-assisted pulsed gradient chemical vapor deposition (PVDC) to load silicon, enabling uniform silicon distribution and preventing silicon particle agglomeration (particle size controlled within 5-10 nm), thus improving material utilization (first-time efficiency >91%). This is because the CVD process uses plasma-assisted decomposition to allow silane precursors to nucleate directionally within the MOF pores, combined with gradient temperature control to achieve atomically uniform deposition (EDS surface scan shows silicon distribution uniformity >95%). Simultaneously, silicon deposition protects the pore structure; the porosity of the lithium-ion battery anode material remains >85% after deposition, maintaining lithium-ion transport channels. This is due to the formation of silicon quantum dots during the low-temperature pre-decomposition stage (300-400℃), preventing MOF framework collapse caused by high temperatures (>600℃) (XRD shows MOF crystallinity remains >90%). Compared to traditional ball milling mixing methods that lead to silicon particle blockage at the pore openings (porosity <70%), this invention achieves precise silicon-pore matching through in-situ deposition using plasma-assisted pulsed gradient chemical vapor deposition.
[0114] The above description is merely a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and variations that are directly derived or conceived by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included within the protection scope of the present invention.
Claims
1. A method for preparing a lithium-ion battery anode material based on a metal-organic framework silicon material, characterized in that, The preparation method includes the following steps: (1) Preparation of MOF materials: Zinc ions and organic ligands are dissolved in a solvent to obtain a precursor solution, and then the MOF precursor is obtained by solvothermal reaction. After drying, the MOF material is obtained. (2) Deposition of silicon material: Silicon material is uniformly distributed in the pores of MOF material using plasma-assisted pulsed gradient chemical vapor deposition to obtain MOF-Si material; The plasma-assisted pulsed gradient chemical vapor deposition method is implemented in three steps, including a silicon material pre-decomposition stage, a diffusion stage, and a crystallization process. (3) Preparation of carbon coating layer: A carbon coating layer is formed on the surface of MOF-Si material by chemical vapor deposition or high temperature pyrolysis, and after high temperature annealing, MOF-Si-C composite material is obtained, which is the negative electrode material of lithium-ion battery. In step (3), the carbon coating layer has a three-layer structure, consisting of a PDA transition layer, a graphene layer, and a carbon nanotube network layer from the inside out.
2. The preparation method according to claim 1, characterized in that, In step (1), the organic ligand is selected from either terephthalic acid or 2-methylimidazole; the solvent is selected from either DMF or methanol; the concentration of zinc ions in the solvent is 0.1-0.5 mol / L; and the molar ratio of zinc ions to organic ligand is 1:1-3.
3. The preparation method according to claim 1, characterized in that, In step (1), the reaction temperature is 80-150℃; the pressure is 0.5-3 MPa; the time is 12-48 h; the drying method is supercritical CO2 drying technology, the temperature is 40-60℃, and the time is 6-12 h.
4. The preparation method according to claim 1, characterized in that, In step (2), the silicon material includes either silicon nanoparticles or silane precursors.
5. The preparation method according to claim 1, characterized in that, In step (2), the flow rate of the silicon material in the pre-decomposition stage is 8-10 sccm, the temperature is 300-400 ℃, the deposition rate is 0.8-1.0 nm / min, and the deposition time is 30-50 min; The diffusion stage employs a three-temperature gradient control, with a heating rate of 4-6 °C / min. The temperature is first increased from 300 °C to 440-460 °C, held for 30-50 min, and then further increased to 540-560 °C. H2 carrier gas is used to propel the silicon material through the mesoporous channels of the MOF material, with a processing time of 60-80 min. The flow rate of H2 is 15-25 sccm. The crystallization process employs pulsed Si₂H₆-assisted gas combined with laser irradiation to induce silicon atom directional rearrangement; the crystallization temperature is 540-560 ℃, and the time is 30-50 min; the pulse period is 10 s on / 5 s off; the laser irradiation wavelength is 520-540 nm, and the power density is 25-35 mW / cm². 2 .
6. The preparation method according to claim 1, characterized in that, The thickness ratio of the PDA transition layer, the carbon nanotube network layer, and the graphene layer is 2:3:8; the thickness of the carbon coating layer is 13-15 nm.
7. The preparation method according to claim 1, characterized in that, In step (3), the MOF-Si-C composite material has a multi-level pore structure, including micropores, mesopores and macropores; the porosity of the MOF-Si-C composite material is >85%.
8. The preparation method according to claim 7, characterized in that, The proportion of micropores is 60-65%; the proportion of mesopores is 30-35%; and the proportion of macropores is 5-10%.
9. The application of a lithium-ion battery anode material prepared by the preparation method according to any one of claims 1-8, characterized in that, The lithium-ion battery anode material is used to prepare lithium-ion battery anode sheets.
10. The application according to claim 9, characterized in that, The application method is as follows: the lithium-ion battery negative electrode material, conductive agent and binder are mixed and made into a slurry, coated on copper foil, and after drying and pressing, a lithium-ion battery negative electrode sheet is obtained.
Citation Information
Patent Citations
Preparation method of nitrogen-doped ordered porous carbon coated silicon nanometer composite material
CN107317011A
Multilayer coated silicon carbon material and preparation method and application thereof
CN118867190A